Analisis Posisi Hukum Saldo Top-Up pada Emoney Sebagai Simpanan Dana Konsumen dalam Perspektif Undang-Undang Perbankan: Penelitian - Lidia Simanjuntak; Nin Yasmine Lisasih (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research is motivated by the unclear legal status of e-money top-up balances and e-commerce stored balances, which function as consumer funds but lack legal certainty under banking regulations, leading to two research questions regarding consumer legal protection and the legal obligations of e-commerce, analyzed through a normative legal research method using statutory, conceptual, and case approaches supported by legal protection theory and consumer protection theory. The first discussion shows that e-money balances are not categorized as bank deposits and are therefore not guaranteed by the Deposit Insurance Corporation, while Bank Indonesia’s float fund regulation provides limited protection that still leaves a normative gap for consumers. The second discussion demonstrates that e- commerce platforms offering stored balances are legally required to segregate consumer funds, apply prudential standards, ensure transparency, and provide compensation mechanisms in accordance with the Banking Act and the Consumer Protection Act. This study concludes that legal protection for e-money balances is not yet optimal and that e- commerce obligations are not fully implemented, recommending regulatory harmonization among the Banking Act, the Electronic Money Regulation, and the Consumer Protection Act, along with strengthened guarantee and dispute resolution mechanisms for consumers.